Formalistic Art Practice in Visual Ethnography : Songket Rajang as A Case Study - Yu, Wei Chow (Universiti Malaysia Sarawak (UNIMAS), 2021)
Visual had played an important role in our daily lives and it was the matter of time before the social science researcher decided to apply visuals in their cultural studies. Hence, the introduction of a new method known as visual ethnography. Visual ethnography accommodates visuals such as photography and videography in enhancing their research documentation. However, the visual approach adapted by the ethnographers has yet to achieve their full potential with the lack of visual aspect presented in the visual data collected; indicating that the researchers did not focus on the image making process. This was due to the conventional method practiced by the social science researchers where they treat visual data as supportive evidence for the written texts; hence neglecting the importance of documenting visual aspect in the visual data. In contradict, the visual approach practiced by the visual arts researchers were able to produce visual data that exhibit visual aspect and interacts with the audience by applying visual arts disciplines and practices. The integration of art practice in ethnographic researches had shown significant outcome; and one of the practices applied was formalistic art practice. Thus, a visual ethnography research with Songket Rajang as case study was conducted through the implementation of formalistic art practice reflexively. With the application of formalistic art practice, the researcher was able to produce aesthetic expressive ethnographic visual representation of Songket Rajang. This research has proven that with the involvement of visual arts practices not only gave a new purpose for the visual data collected, but also introduced a new approach in visual research; proving the contribution of visual arts in research field.